2014
DOI: 10.1074/jbc.m114.575621
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Breakdown Contributes to Immune Defense against Group A Streptococcus

Abstract: Background:The role of hyaluronan catabolism in group A Streptococcus (GAS) infection has not been studied. Results: Hyaluronan size differentially influenced GAS infection in vitro and in mice. Conclusion: Digestion of hyaluronan derived from either the bacterium or host enhances host immune defense. Significance: Digestion of hyaluronan during GAS infection may be a previously unrecognized mechanism for host defense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 35 publications
(44 reference statements)
0
17
1
1
Order By: Relevance
“…Large-molecular weight HA is highly abundant and is the major component of the ECM (Tammi et al, 1994). HA digestion into small fragments after injury has been shown to have important implications for inflammatory responses in vivo (Jiang et al, 2005;Muto et al, 2014;Noble et al, 1996;Taylor et al, 2004) and can modify infection by GAS through digestion of the HA-rich bacterial capsule of this organism (Schommer et al, 2014). However, a clear understanding of the mechanism responsible for HA catabolism or its connection to host antimicrobial defense has not been previously defined.…”
Section: Discussionmentioning
confidence: 99%
“…Large-molecular weight HA is highly abundant and is the major component of the ECM (Tammi et al, 1994). HA digestion into small fragments after injury has been shown to have important implications for inflammatory responses in vivo (Jiang et al, 2005;Muto et al, 2014;Noble et al, 1996;Taylor et al, 2004) and can modify infection by GAS through digestion of the HA-rich bacterial capsule of this organism (Schommer et al, 2014). However, a clear understanding of the mechanism responsible for HA catabolism or its connection to host antimicrobial defense has not been previously defined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that inactivation in hyaluronate lyase (HylA) restored full encapsulation in partially encapsulated M-4 GAS strains, thus demonstrating the mutually exclusive interaction between the hyaluronan capsule and active hyaluronidase (32). In addition, Schommer et al demonstrated in a mouse model that the difference in capsule size was regulated by bacterial hyaluronidase and that the high molecular mass of the hyaluronan capsule influences GAS virulence by facilitating deep tissue infections (34). Based on our findings, we hypothesize that inactivation of HylP.2 could determine a different encapsulation (i.e., capsule sizing) of M-18 GAS strains, thus resulting in a more virulent clone.…”
Section: Discussionmentioning
confidence: 99%
“…GAGs are widely distributed and function in cellular and extracellular signalling in all biological processes. Bacteria express GAGs and are used to inhibit phagocytosis by increasing molecular weight; for example, Streptococcus has a cellular coating of high-molecular weight hyaluronan [68]. Manipulation of GAGs, by removal of heparin sulfate or reducing its synthesis, inhibits attachment of S. aureus and S. pneumonia in lung epithelial cells and fibroblasts [69].…”
Section: The Basement Membrane Matrix In Copdmentioning
confidence: 99%